Refined understanding of street vitality: comparing the spatial effects of pedestrian vitality and cycling vitality and the spatial heterogeneity of factors - Zhaocheng Bai; Shuyu Huang; Lei Wang; Jun Qi (International Journal of Digital Earth)
Street vitality is a key indicator of urban sustainability, and high-quality built environments can promote street vitality. However, existing research lacks refined measurement approaches for street vitality and sufficient understanding of the spatial relationship patterns between built environment and street vitality. This study employs street view images and image detection to achieve a fine-grained measurement of street vitality. Furthermore, it utilizes methods such as the Optimal Parameter Geographical Detector, Spatial Lag Model, and Multi-scale Geographically Weighted Regression to explore the relationships between built environment factors and both pedestrian and cycling vitality, and to identify their distribution patterns and spatial effects. The findings reveal that: (1) there are significant differences in the distribution of pedestrian and cycling vitality, with varying associations with built environment factors; (2) the relationships between built environment factors and the two types of vitality differ inside and outside scenic areas; (3) both forms of vitality exhibit clear spatial lag effects, with approximately one-third of the vitality values correlated with adjacent areas; and (4) the correlation between built environment factors exhibits spatial heterogeneity. This study provides refined understanding of street vitality, offering guidance for street renewal.